Product sophistication and spillovers from foreign direct investment. (23rd December 2016) - Eck, Katharina; Huber, Stephan
Abstract: Foreign direct investment (FDI) in developing countries is often associated with higher economic growth due to knowledge and technology spillovers to local firms. One way that FDI speeds up growth is by facilitating the manufacturing of more sophisticated products by local firms. So far, there is a lack of firm‐level evidence how the presence of multinational firms affects the product sophistication of firms in a developing country. The aim of this paper is to fill this gap. We compile an extensive firm–product‐level data set of Indian manufacturing firms, which we complement with information on product sophistication and spillovers from FDI. We then explore different channels through which spillovers from multinationals to local Indian firms foster the manufacturing of sophisticated products. We find evidence that spillovers through supplier linkages strongly increase the manufacturing of sophisticated products in India. Résumé: Sophistication des produits et effets de retombée de l'investissement direct de l'étranger . L'investissement direct de l'étranger (IDE) vers les pays en voie de développement est souvent associé à une plus forte croissance économique à cause de transfert de connaissances et des effets de retombée de la technologie sur les firmes locales. Une manière pour l'IDE d'accélérer la croissance est de faciliter la manufacture de biens plus sophistiqués par les firmes locales. Pour le moment, il y a manque de données probantes au niveau des firmes montrant comment la présence de firmes plurinationales affecte la sophistication des produits des firmes domestiques dans les pays en développement. Ce mémoire veut combler ce vide. On compile des données extensives pour les produits des firmes manufacturières indiennes qu'on complète avec des données sur la sophistication des produits et les effets de retombée des IDE. On explore alors les différents canaux à travers lesquels des effets de débordements des plurinationales se déversent sur les firmes indiennes et suscitent la production de biens sophistiqués. Les résultats montrent que les retombées via des liens avec les fournisseurs accroissent fortement le degré de sophistication des produits en Inde.